Auditory- and Vestibular-Evoked Potentials Correlate with Motor and Non-Motor Features of Parkinson’s Disease - Shalash, Ali Soliman; Hassan, Dalia Mohamed; Elrassas, Hanan Hani; Salama, Mohamed Mosaad; Méndez-Hernández, Edna; Salas-Pacheco, José M.; Arias-Carrión, Oscar (Frontiers in Neurology, 2017)
Degeneration of several brainstem nuclei has been long related to motor and non-motor symptoms of Parkinson's disease (PD). Nevertheless, due to technical issues, there are only a few studies that correlate that association. Brainstem auditory-evoked potentials (BAEP), and vestibular evoked myogenic responses (VEMPs) represent a valuable tool for brainstem assessment. Here, we investigated the abnormalities of BAEPs, ocular and cervical VEMPs (oVEMPs and cVEMPs) in patients with PD and its correlation to the motor and non-motor symptoms. Fifteen patients diagnosed as idiopathic PD were diagnostic using Unified Parkinson’s Disease Rating Scale (UPDRS) and its subscores, Hoehn and Yahr scale, Schwab and England scale, and Non-Motor Symptoms Scale (NMSS). PD patients underwent pure-tone, speech audiometry, and tympanometry, BBAEP, and ocular and cervical VEMPs and compared to fifteen age-matched control subjects. PD subjects showed abnormal BAEPs wave morphology, prolonged absolute latencies of wave V and I-V interpeak latencies. Absent responses were the marked abnormality seen in oVEMP. Prolonged latencies with reduced amplitudes were seen in cVEMP responses. Rigidity and bradykinesia were correlated to the BAEPs and cVEMPs responses contralateral to the clinically more affected (CMA) side. Contralateral and ipsilateral cVEMPs were significantly correlated to sleep (p=0.03 & 0.001), perception (p=0.03), memory / cognition (p=0.025), and urinary scores (p=0.03). The oVEMP responses showed significant correlations to cardiovascular (p= 0.01) and sexual dysfunctions (p=0.013). PD is associated with BAEPs and VEMPs abnormalities that are correlated to the motor and some non-motor clinical characteristics. These abnormalities could be considered as potential electrophysiological biomarkers for brainstem dysfunction and its associated motor and non-motor features.